Run the race [videorecording (DVD)] - Dowling, Chris; Stine, Tanner, 1995-; Polaha, Kristoffer, 1977-; Hofer, Evan; Van Peebles, Mario; Fisher, Frances, 1952- (Universal Pictures Home Entertainment, 2019)
Reeling from his mother's death and his father's abandonment, Zach, an All-State athlete, finds glory on the football field, working to earn a college scholarship and the brothers' ticket out of town. When a devastating injury puts Zach and his dreams on the sidelines, David laces up his track cleats to salvage their future and point Zach toward hope.